Inhibition of copper corrosion in domestic water applications - Romano, Michelle S. (2009)
Copper is the second largest tonnage metal used by man. Owing to its malleability, ductility and thermal conductivity, it is used extensively in plumbing systems to convey high temperature domestic water. Like all metals, however, copper is susceptible to corrosion. Many preventive measures have been carried out to address this problem, one of which is the application of inhibitors. These are chemicals added to the system, which will if not mitigate, retard the corrosion process. This study investigates the viability of applying L-cysteine, EDTA and adenine as inhibitors for copper corrosion at an elevated temperature. Corrosion studies are carried out via the electrochemical polarization technique in two types of domestic water-hard and soft water. These chemicals are added at three levels of concentration 5x10-4M, 1x10-3M and 1x10-2M. Results show that L-cysteine is effective in both hard and soft water. In soft water however, inhibition is attained only at a concentration of 1x10-2 M. EDTA is effective in hard water, with a concentration of 5x10-4M yielding the highest inhibition efficiency. Higher concentrations of 1x10-3 M and 1x10-2 M lower its corrosion inhibition property. This is attributed to the change in pH it produces. Acidic solutions render it ineffective. In soft water, this compound is inefficient, because even small additions produce highly acidic solutions. Adenine is able to inhibit corrosion in hard water at small concentrations, i.e. 5x10-4 M. Increasing the concentration does not yield significant effects. On the other hand, it does not affect the uniform corrosion of copper in soft water.